OPTIMIZATION OF CULTURAL CONDITIONS FOR THE PRODUCTION OF PRODIGIOSIN BY SERRATIA MARCESCENS AND SCREENING FOR THE ANTIMICROBIAL ACTIVITY OF PRODIGIOSIN - DR. D. GEETHA RAMANI; AMRITHA NAIR; K. KRITHIKA (International Journal of Pharma and Bio Sciences, 2014)
Prodigiosin are a group of natural pigments produced by Serratia marcescens. The pigment is produced by various bacteria like Pseudomonas magneslorubra, Vibrio psychroerythrous, Streptomyces spectabilis, etc., This pigment is known for its anti bacterial, antifungal, antiprotozoan and anticancer activity. The present investigation focuses on the optimization of cultural parameters like incubation period, pH, oils, cultural media, and carbon and nitrogen sources, to enhance the production of Prodigiosin from S.marcescens, followed by its chromatographic analysis.